Posterior Medial Meniscus Root Repair With Peripheral Stabilization Stitch - Daniel J. Liechti MD; Nicholas Kennedy MD; Riley Kramer BS; Robert F. LaPrade MD, PhD (SAGE Publishing, 2023)
Background: Posteromedial meniscal root tears occur when the meniscal root detaches from the tibial plateau, which limits the native functionality of the meniscus, alters tibiofemoral contact forces, and can progress to meniscal extrusion. Untreated meniscal root tears with meniscal extrusion have been associated with significant articular cartilage loss and accelerated progression of osteoarthritis. Recent biomechanical evidence suggests restoring the contact area with the use of a peripheral stabilization suture at the posteromedial aspect of the tibial plateau. Indications: Meniscal root repair with a peripheral stabilization suture is indicated by clinical and radiographic evidence of complete detachment of the posteromedial meniscus root with significant meniscal extrusion outside the joint. Technique Description: This technique uses 2 tunnels for the meniscal root repair as well as a single additional transtibial tunnel for the peripheral stabilization suture. The described technique demonstrates a peripheral release along the meniscocapsular junction to allow the meniscus to be reapproximated to its anatomical attachment site. This is followed by transtibial tunnel preparation to allow suture passage for the meniscal root repair and an additional transtibial tunnel is created for the peripheral stabilization suture. After stabilization of the extruded meniscus, the suture is tied down over a cortical fixation device on the anteromedial tibia. Results: Significant improvement has been reported by clinical studies after the transtibial pullout repair method; however, structural outcomes have shown conflicting results. Kaplan et al reported patients treated with transtibial suture pullout technique with 2 locking cinch sutures had improved clinical outcomes, but increased extrusion of the medial meniscus compared with the preoperative state, whereas Kim et al reported a decrease in meniscal extrusion following pullout suture repair technique. Discussion: Posteromedial meniscus root repair using a peripheral stabilization suture is an effective surgical technique to restore the contact pressures of the knee and limit the amount of meniscal extrusion. This allows for appropriate correction of hoop stress to prevent further cartilage loss and progression of osteoarthritis. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.